Identification of Quantitative Trait Loci for Clubroot Resistance in Brassica oleracea With the Use of Brassica SNP Microarray - Peng, Lisha; Zhou, Lili; Li, Qinfei; Wei, Dayong; Ren, Xuesong; Song, Hongyuan; Mei, Jiaqin; Si, Jun; Qian, Wei (Frontiers in Plant Science, 2018)
Increasing clubroot resistance (CR) of Brassica oleracea by ascertaining the molecular mechanisms has been the key focus in modern B. oleracea breeding. In order to identify the quantitative trait loci (QTLs) associated with CR in B. oleracea, 94 F2 vegetative lines which were developed by tissue culture of selfed seeds from the F1 generation between a clubroot-resistant B. oleracea inbred line and a susceptible line, were identified for disease incidence and six CR-associated traits under a lab inoculation by Plasmodiophora brassicae and were genotyped with the 60K Brassica SNP array. Significant correlations were detected for numbers of fibrous roots and P. brassicae content in roots two traits with DIdisease incidence. Nine linkage groups were constructed from 565 bins which covered around 3,000 SNPs, spanning 1,028 cM of the B. oleracea genome with an average distance of 1.82 cM between adjacent bins. A total of 23 QTLs were identified for disease incidence and the other two correlated traits, individually explaining 6.1-17.8% of the phenotypic variation. Several overlaps were detected among traits, including one three-traits-overlapped locus on linkage group C08 and two important overlapped regions between the two CR-associated traits on C06. The QTLs were compared with known CR loci/genes and the novelty of our QTLs was discussed